Doktrinisasi Kitab Ta’lim Al-Muta’allim dalam Aktifitas Belajar Santri di Pondok Pesantren Darussalam Sumbersari Kencong Kepung Kediri - Haryadi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Pondok Pesantren is an institution that creates human resources who are devout and have good character, have a mature emotional soul, think healthy and have a strong spirit of jihad in nashr al-ilmi wa al-din which is oriented towards the happiness of living in the world until the hereafter . To achieve this, of course, a concept is needed in learning activities for students as a learning support factor. The research used qualitative research methods, while the data collection techniques were participant observation, in-depth interviews and documentation. This can largely ignore that; First, teaching and learning activities at the Darussalam Sumbersari Islamic Boarding School are carried out both classically and non-classical (halaqah-halaqah). There are methods of processing /delivery using wetonan, bandongan, sorogan, syawir / bahtsul-masail. Second, the doctrine related to the study of Ta'lim Muta'allim's studies on student learning, that there are indeed special efforts from the masyayikhs and universities in realizing the doctrine of the study of the Ta'lim al-Muta'allim Book in institutional activities such as making Ta'lim a compulsory study. For all students, the intention is to get together before starting to study every time they enter the madrasa, the imposition of compulsory study hours, evening takror and so on.